INFLUENCE OF DIFFERENT LEADERSHIP STYLES ON EMPLOYEE MOTIVATION (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the influence of changing leadership styles on employee perception and motivation within organizations. Utilizing a quantitative approach, data was collected through Likert-based questionnaires distributed among 331 employees across various industries. The findings reveal a positive perception of employees towards changing leadership styles, emphasizing the importance of leaders' adaptability and communication transparency. Furthermore, the study demonstrates a significant influence of changing leadership styles on employee motivation, highlighting the role of leaders in driving employee engagement and performance. These findings underscore the need for organizations to prioritize leadership development initiatives aimed at enhancing leaders' adaptability and communication skills to effectively navigate organizational change and inspire employee motivation.